Talking with Jon Sobrino (Journal of Parents and Teachers, 2014)
In this article of Parents and Teachers an interview with Jon Sobrino is offered, where topics such as current society, the education needed in this society, solutions to problems or education in Latin America are discussed.
Keywords: interview; Jon Sobrino; Latin America; society; current education.